Dietary pattern, dietary total antioxidant capacity, and dyslipidemia in Korean adults - Seong-Ah Kim; Hyojee Joung; Sangah Shin (Nutrition Journal, 2019)
Abstract Background Abnormal diet is considered to be an important risk factor for dyslipidemia. However, so far, most studies have focused on the association between single factors only, such as specific nutrients, foods, or dietary patterns, and dyslipidemia risk. This study aimed to examine the association of the joint interaction between dietary pattern and dietary total antioxidant capacity (TAC) with dyslipidemia. Methods We performed a dietary pattern analysis and calculated the dietary TAC based on 24-h dietary recall (DR) data from Korea National Health and Nutrition Examination Survey (KNHANES) 2007–2012, which is representative population-based cross-sectional survey in Korea. A total of 29,624 participants aged over 19 years were included for the analysis. The number of people with hypercholesterolemia, hypertriglyceridemia, and hypoHDL-cholesterolemia was 3703, 3513, and 9802, respectively. We examined the association between the joint classifications of dietary pattern score tertiles and dietary TAC level tertiles and dyslipidemia. Results Our results demonstrated that the “Rice & Kimchi” pattern was associated with low prevalence of hypercholesterolemia, and high prevalence of hypertriglyceridemia and hypoHDL-cholesterolemia; whereas the pattern of both “Oil, sweets, fish & other vegetables” and “Grain, bean, nuts, vegetables & fruits” were associated with low prevalence of hypertriglyceridemia. Also we demonstrated that for all dietary patterns except for the “Grain, bean, nuts, vegetables & fruits”, dietary TAC was inversely associated with hypertriglyceridemia. Conclusion This study provides basic data for the lipid-lowering effect of dietary TAC and its interaction with dietary patterns. Further study will be needed to investigate the association between dietary TAC and dietary patterns with other diseases like metabolic syndrome, cardiovascular disease, or cancer.